COMT Genotype and Efficacy of Propranolol for TMD Pain: A Randomized Trial. (February 2021) - Slade, G.D.; Fillingim, R.B.; Ohrbach, R.; Hadgraft, H.; Willis, J.; Arbes, S.J.; Tchivileva, I.E.
Propranolol is a nonselective β-adrenergic receptor antagonist that is efficacious in reducing facial pain. There is evidence that its analgesic efficacy might be modified by variants of the catechol-O-methyltransferase ( COMT ) gene. We tested the hypothesis in a subset of 143 non-Hispanic Whites from a randomized controlled trial of patients with painful temporomandibular disorder (TMD). Patients were genotyped for rs4680, a single nucleotide polymorphism of COMT, and randomly allocated to either propranolol 60 mg twice daily or placebo. During the 9-wk follow-up period, patients recorded daily ratings of facial pain intensity and duration; the product was computed as an index of facial pain. Postbaseline change in the index at week 9 (the primary endpoint) was analyzed as a continuous variable and dichotomized at thresholds of ≥30% and ≥50% reduction. Mixed models for repeated measures tested for the genotype × treatment group interaction and estimated means, odds ratios (ORs), and 95% confidence limits (95% CLs) of efficacy within COMT genotypes assuming an additive genetic model. In secondary analysis, the cumulative response curves were plotted for dichotomized reductions ranging from ≥20% to ≥70%, and genotype differences in area under the curve percentages (%AUC) were calculated to signify efficacy. Mean index reduction did not differ significantly ( P = 0.277) according to genotype, whereas the dichotomized ≥30% reduction revealed greater efficacy among G:G homozygotes (OR = 10.9, 95%CL = 2.4, 50.7) than among A:A homozygotes (OR = 0.8, 95%CL = 0.2, 3.2) with statistically significant interaction ( P = 0.035). Cumulative response curves confirmed greater ( P = 0.003) efficacy for G:G homozygotes (%AUC difference = 43.7, 95%CL = 15.4, 72.1) than for A:A homozygotes (%AUC difference = 6.5, 95%CL = -30.2, 43.2). The observed antagonistic effect of the A allele on propranolol's efficacy was opposite the synergistic effect hypothesized a priori. This unexpected result highlights the need for better knowledge of COMT's role in pain pathogenesis if the gene is to be used for precision-medicine treatment of TMD (ClinicalTrials.gov NCT02437383).